Manganese-porphyrin-enhanced MRI for the detection of cancer cells: A quantitative in vitro investigation with multiple clinical subtypes of breast cancer. - Mosa Alhamami; Weiran Cheng; Yuanyuan Lyu; Christine Allen; Xiao-An Zhang; Hai-Ling Cheng (PLoS ONE)
Magnetic resonance imaging (MRI) contrast agents (CAs) are chemical compounds that can enhance image contrast on T1- or T2- weighted MR image. We have previously demonstrated the potential of MnCl2, a manganese-based CA, in cellular imaging of breast cancer using T1-weighted MRI. In this work, we examined the potential of another class of manganese-based CAs, manganese porphyrins (MnPs), for sensitive cellular detection of multiple clinical subtypes of breast cancer using quantitative MRI. Using a clinical 3.0-T MRI scanner, the relaxivities of two MnPs, MnTPPS4 and MnTPPS3NH2, and conventional Gd-DTPA (control) were measured in ultrapure water and their T1 contrast enhancement patterns were characterized in multiple clinical subtypes of breast cancer. The toxicity of the three CAs was evaluated in vitro. Compared to Gd-DTPA, both MnTPPS3NH2 and MnTPPS4 enabled a more sensitive multi-subtype detection of four breast cell lines at doses that posed no cytotoxic effects, with MnTPPS3NH2 producing the greatest positive enhancement. The superior T1 enhancement capabilities of MnPs over Gd-DTPA are statistically significant and are likely due to their greater cellular uptake and relaxivities. The results demonstrate that multiple clinical subtypes of breast cancer can be imaged on a 3.0-T MRI scanner using MnPs as T1 cellular CAs.